Impact of seed transmission of Alternaria alternata (Fr.) Keissler on seedquality and yield of chickpea - BHARGAVA, P.K. (Indian Phytopathology, 2002)
Culture filtrate of A. alternata (causal agent of chickpea blight) inhibited seed germination, plumule growth and caused blackening of seed in developing pods. The disease caused significant loss of flowers, pods and seeds in big seeded cultivar JG1265 but yield losses were greater in small seeded cultivar C 235. Sowing of diseased seeds lowered the yield. Significantly higher emergence was obtained when diseased seeds were separated (graded) and treated before sowing. Seed dressing with mancozeb resulted in max. emergence and yield, whereas triforine was most effective as a foliar spray. For integrated disease management sowing of disease, free treated seed followed by sprays of di-ammonium phosphate at 45 and 65 d were effective in minimizing disease incidence and increasing yield.